40Ar/39Ar ages and geological significance of Neoproterozoic–Cambrian mafic rocks in the Aksu–Wushi area, NW Tarim Craton. (26th November 2018) - Lu, Yuanzhi; Zhu, Wenbin; Jourdan, Fred; Ge, Rongfeng; Cui, Xiang; Wen, Bin
Abstract : Mafic dyke swarms and continental flood basalts record crucial information on mantle dynamics, crustal palaeostress, and supercontinent cycle. However, these mafic rocks are relatively difficult to date using zircon U–Pb methods because autogenous magmatic zircons are rare or absent in the rapidly cooled mafic magmas and most zircons extracted from these rocks are likely captured from their wall rocks. One good example of this dilemma is the Precambrian mafic dykes and layered basites in the Aksu–Wushi area, NW Tarim Craton, from which abundant zircon U–Pb data have yielded age spectra similar to those of the detrital zircons from the associated (meta‐)sedimentary rocks. In this paper, we performed the first 40 Ar/ 39 Ar dating on separated mineral grains from the mafic dykes (plagioclase and amphibole) and layered basites (plagioclase and pyroxene) in this area. Amphiboles from a mafic dyke cross‐cutting the blueschist‐bearing Aksu Group yielded a 40 Ar/ 39 Ar plateau age of 744.5 ± 2.8 Ma, whereas pyroxenes from a layered basite within the Sugetbrak Formation yielded a 40 Ar/ 39 Ar plateau age of 521.0 ± 2.1 Ma. The 40 Ar/ 39 Ar plateau age of 744.5 ± 2.8 was interpreted as the crystallization age of the studied mafic dykes and provides a minimum constraint for the third phase of deformation of the blueschist terrane. The mini‐plateau age of 521.0 ± 2.1 Ma was interpreted as a minimum crystallization age for basite of the Sugetbrak Formation. We also conducted geochemical analyses on layered basites of the Sugetbrak Formation from the Xiaoenbrak Formation, and the results indicated that these layered basites shared a uniform geochemical characteristic. Combining geochronological and geochemical analyses, we propose that the basites of the Sugetbrak Formation probably recorded a rifting event on the north‐western margin of the Tarim Craton during Early Cambrian.